Does Interest Rate Impact Economic Growth? Empirical Insight from Nepal - Budhathoki, Prem Bahadur; Bhattarai, Ganesh; Upadhyaya, Yadav Mani (Nepal Journal of Multidisciplinary Research, 2024)
Background: The relationship between interest rates, inflation, and non-performing loans on economic growth is debated in theoretical and empirical research. Hence, the study examines the effect of interest rate, inflation rate, and non-performing loans on the economic growth in Nepal. Methods: The paper incorporated quarterly data spanning nine years (2011-2019) and consisted of 972 observations. The study collected secondary data from the official websites of Nepal Rastra Bank and the Ministry of Finance, Nepal. The study used a panel cointegration test and random-effect models to examine the long-run relationship between predictor and response variables. Results: The impact of lending rate (LR) on economic growth is positive and statistically significant (β1 = 0.017, p < .01) in Nepal. Similarly, the coefficient of LNCPI (β2 = 0.687, p < .01) suggests that there is a positive relationship between the Consumer Price Index (CPI) and the Gross Domestic Product (GDP). The regression coefficient of CPI (β3 = -.001, p > .05) suggests that an increase in non-performing loans (NPL) led to a decrease in GDP. However, this relationship was not statistically significant for the Nepalese Economy. Conclusion: The study concludes that the interest and inflation rates positively affect Nepal's economic growth. The findings indicate that policymakers, such as Nepal Rastra Bank, should maintain interest rates at an appropriate level. Novelty: This study is novel because it thoroughly analyzes numerous observations over long periods to investigate the impacts of loan rates, inflation rates, and non-performing loans on economic growth in Nepal, improving its generalizability.